PENGARUH KUALITAS SDM DAN KOMPETENSI TERHADAP KINERJA PERSONEL SATRESKRIM POLRES PAMEKASAN YANG DIMEDIASI OLEH MOTIVASI - Chamariyah; Wahyu Dwi Purnomo; C. Sri Hartati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Wahyu Dwi Purnomo, 2022. The influence of HR quality and HR competence on the performance of Pamekasan Police Satreskrim personnel mediated by motivation. Postgraduate Program at Wijaya Putra University, Surabaya. This type of research is explanatory research, the approach uses a quantitative approach, data analysis uses Partial Least Square (PLS). The research sample was 65 people. The aims of this research are 1). To determine and analyze the direct influence of the quality of human resources on the performance of the Satreskrim Polres Pamekasan personnel; 2). To find out and analyze the direct influence of competence on the motivation of the Satreskrim Polres Pamekasan; 3). To find out and analyze the direct influence of the quality of human resources on the motivation of the Satreskrim Polres Pamekasan; 4). To find out and analyze the direct influence of competence on the motivation of the Satreskrim Polres Pamekasan; 5). To find out and analyze the direct influence on the performance of the Satreskrim Polres Pamekasan personnel; 6).To determine and analyze the direct influence of the quality of human resources on the performance of the Satreskrim Polres Pamekasan personnel mediated by motivation; 7) To find out and analyze the direct influence of competence on the performance of Satreskrim Polres Pamekasan personnel which is mediated by motivation. Smart PLS version 3.0 analysis tool, research variables include independent variables: HR quality and HR competence, personnel performance monitoring variables, mediating variables: motivation.